FEATURES OF THE JUDICIAL SYSTEM IN THE UK - Sansyzbaykzy, Салтанат (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
One of the most active members of the world community is the UK with its centuries-old traditions of justice. Despite numerous reforms, the judicial system of great Britain, is a sophisticated complex of various judicial institutions, legal norms, customs and traditions. Centuries-old experience of development of the judicial system in the UK is of great practical interest for researchers. In this regard, this article analyzes the principles of formation and structure of the English judicial system. The main trends of changes in the judicial system of great Britain in the second half of the twentieth century and after the country's entry into the EU.